Diagnostic Accuracy of MRI and CT Scan Features in Differentiation of Pediatric Ependymoma from Medulloblastoma - Mirfendereski, Sam; Mansouri, Neda (Iranian Journal of Child Neurology, 2025)
Objectives The study aims to compare the diagnostic accuracy of MRI and CT scan features in differentiating medulloblastoma from ependymoma, two similar pediatric brain tumors. Materials & Methods This retrospective cross-sectional study was conducted on all pediatric patients with posterior fossa tumors admitted to teaching hospitals affiliated with Isfahan University of Medical Sciences from 2017 to 2022. Forty-three patients with posterior fossa tumors were identified, and seven patients were excluded due to diagnoses other than medulloblastoma or ependymoma. Tumor morphology on MRI, tumor density on CT scan, and apparent diffusion coefficient (ADC) values were assessed to differentiate medulloblastoma from ependymoma. Results Histopathologic diagnosis was medulloblastoma in 21 patients (60%) and ependymoma in 14 patients (40%). Mean ADC values in medulloblastoma and ependymoma cases were 0.67±0.19 (range= 0.50-1.25) and 1.22±0.29 (range=0.67-1.72), showing a significant statistical difference between the two groups (p-value=0.000). The ADC cut-off point of 0.9825 was associated with 90% sensitivity and 92.9% specificity for differentiation of ependymoma from medulloblastoma. Conclusion While tumor morphology on MRI and other studied parameters are unreliable for differentiating medulloblastoma and ependymoma, ADC values may provide a potential diagnostic tool. Further studies are needed to confirm the utility of DWI and other advanced MRI techniques in differentiating these tumors